Self-determination theory and the psychology of exercise - Hagger, Martin; Chatzisarantis, N. (Routledge, 2008)
The purpose of the Self-determination Theory is to explain motivation and behaviour based on individual differences in motivational orientations, contextual influences, and interpersonal perceptions. The theory has shown utility in explaining the antecedents and processes that underpin exercise behaviour. This review will provide an overview of the theory and its application in explaining health-related exercise motivation, behaviour, and outcomes. Recent innovative research using the theory in exercise contexts will also be reviewed in two key areas: advances in measurement and theoretical integration. Based on this evidence, recommendations for future investigations will be made advocating the development instruments to measure self-determined motivation from first principles, the adoption of experimental and intervention designs to better infer causal links between self-determined motivation and behaviour, further investigation of the role of implicit self-determined motivation in predicting behaviour, and the integration of the Self-determination Theory with other theories of motivation, e.g. the Theory of Planned Behaviour and the Achievement Goal Theory, to provide complimentary explanations of self-determined motivation in exercise contexts. Based on the evidence, the Self-determination Theory demonstrates considerable efficacy in explaining exercise motivation and behaviour. Future research should adopt these recommendations to develop the theory further with a view to informing intervention and practice.